Discovering Electron‐Transfer‐Driven Changes in Chemical Bonding in Lead Chalcogenides (PbX, where X = Te, Se, S, O). Issue 49 (2nd November 2020) - Maier, Stefan; Steinberg, Simon; Cheng, Yudong; Schön, Carl‐Friedrich; Schumacher, Mathias; Mazzarello, Riccardo; Golub, Pavlo; Nelson, Ryky; Cojocaru‐Mirédin, Oana; Raty, Jean‐Yves; Wuttig, Matthias
Abstract: Understanding the nature of chemical bonding in solids is crucial to comprehend the physical and chemical properties of a given compound. To explore changes in chemical bonding in lead chalcogenides (PbX, where X = Te, Se, S, O), a combination of property‐, bond‐breaking‐, and quantum‐mechanical bonding descriptors are applied. The outcome of the explorations reveals an electron‐transfer‐driven transition from metavalent bonding in PbX (X = Te, Se, S) to iono‐covalent bonding in β‐PbO. Metavalent bonding is characterized by adjacent atoms being held together by sharing about a single electron (ES ≈ 1) and small electron transfer (ET). The transition from metavalent to iono‐covalent bonding manifests itself in clear changes in these quantum‐mechanical descriptors (ES and ET), as well as in property‐based descriptors (i.e., Born effective charge ( Z *), dielectric function ε(ω), effective coordination number (ECoN), and mode‐specific Grüneisen parameter (γTO )), and in bond‐breaking descriptors. Metavalent bonding collapses if significant charge localization occurs at the ion cores (ET) and/or in the interatomic region (ES). Predominantly changing the degree of electron transfer opens possibilities to tailor material properties such as the chemical bond ( Z *) and electronic (ε∞ ) polarizability, optical bandgap, and optical interband transitions characterized by ε2 (ω). Hence, the insights gained from this study highlight the technological relevance of the concept of metavalent bonding and its potential for materials design. Abstract : Systematic changes of chemical bonding in lead chalcogenides (PbX, where X = Te, Se, S, O) are studied to comprehend their properties. The exploration reveals an electron‐transfer‐driven transition from metavalent bonding in PbX (X = Te, Se, S) to iono‐covalent bonding in β‐PbO. The insights gained from this study highlight the technological relevance of the concept of metavalent bonding and its potential for materials design.